24 1 Number Systems
Lemma 1.1 Assume that x ≥ 0, y ≥0, and x
n
= y
n
for some natural number n.
Then x =y.
If x
n
=y
n
=0, then x =y =0 and we are done. If x
n
=y
n
> 0, since x ≥0 and
y ≥0, we have x>0 and y>0 (why?). We have
x
n
−y
n
=(x −y)
n−1
k=0
x
n−1−k
y
k
=0.
Since x and y are strictly positive, the sum in the right-hand side has only strictly
positive terms. Thus, x −y =0, and we have proved Lemma 1.1.
Lemma 1.1 implies that there is at most one solution to x
n
= a.Ifa = 0, it is
clear that there is only the solution x =0. For the rest of the existence proof, we
assume that a>0. Define the set
A =
y>0 :y
n
<a
.
Note that since a>0wehavec =
a
a+1
< 1 (why?) and c>0. By I2 c
n
<c.Note
also that c<a(why?), and so c
n
<c<a. That is, c is in A, and A is nonempty.
Observe now that if t>a+ 1, then by I1 t
n
>(a+1)
n
. Moreover, by I3 (a +
1)
n
>a+ 1 >a, and so t
n
>a.Thus,ift>a+1, then t is not in A. Therefore,
a +1 is an upper bound of A. Since A is bounded above by a +1 and nonempty, it
has a least upper bound that we denote by m.
We want to show that m
n
=a and therefore that m is the unique solution of the
equation x
n
=a. We do a proof by contradiction. We will need the following:
Lemma 1.2 Assume that 0 <x<yand that n ≥2 is a natural. Then
0 <y
n
−x
n
<(y−x)ny
n−1
.
To prove Lemma 1.2, we start with
y
n
−x
n
=(y −x)
n−1
k=0
y
n−1−k
x
k
.
Since 0 <x<y, if we replace x by y in each term of the sum, we get something
bigger. For every integer k between 0 and n −1, we have
x
k
≤y
k
,
and the inequality is strict for k ≥1. Hence,
y
n−1−k
x
k
≤y
n−1−k
y
k
=y
n−1
and
y
n
−x
n
<(y−x)
n−1
k=0
y
n−1
=(y −x)ny
n−1
,
where we use the fact that from k =0ton −1 there are n identical terms in the sum
above. This proves Lemma 1.2.